Effect of flaxseed flour incorporation on the physical properties and consumer acceptability of cereal bars. - Khouryieh, H.; Aramouni, Fadi M. (My University, 2014)
Extensive research has revealed numerous nutritional and health benefits of flaxseed due primarily to its nutrients content. The objective of this study was to evaluate the effect of flaxseed flour addition on the physical and sensory characteristics of cereal bars. Four formulations of the flaxseed cereal bars were prepared by partially replacing oats with flaxseed flour added at levels of 0 (control), 6%, 12% and 18%. There were no significant differences (p>0.05) in water activity, moisture and firmness values between the flaxseed bars and control. Flaxseed addition significantly (p<0.05) decreased lightness and increased redness of the bars. There were no significant differences (p>0.05) between the 12% flax cereal bars and the control with respect to sensory attributes and overall acceptability. The overall acceptability for both 12% flax bars and the control was in between ‘like moderately’ and ‘like slightly’ on the 9-point hedonic scale. The overall acceptability was most highly correlated with flavor acceptability for both control (r¼0.80) and 12% flax (r¼0.82) cereal bars. Flaxseed bars provided 12% dietary fiber of the daily recommended value. These results indicated that flaxseed flour incorporation up to 12% substantially enhanced the nutritional qualities of the cereal bars without affecting their sensory and quality properties.
Keywords: Physical properties; Consumer acceptability; Nutritional composition; Flaxseed; Cereal bars